Study of the Unit-3 nuclear reactor of Fukushima Daiichi by cosmic muon radiography. (31st December 2021) - Fujii, Hirofumi; Hara, Kazuhiko; Hayashi, Kohei; Kakuno, Hidekazu; Kodama, Hideyo; Nagamine, Kanetada; Sato, Kotaro; Kim, Shin-Hong; Suzuki, Atsuto; Sumiyoshi, Takayuki; Takasaki, Fumihiko; Tanaka, Shuji; et al.
Abstract: We have investigated the status of the nuclear debris in the Unit-3 nuclear reactor of the Fukushima Daiichi nuclear power plant by the method called cosmic muon radiography. We used the same telescope system which was used to study the Unit-2 reactor. As in the previous studies, we succeeded in identifying the inner structure of the reactor, such as the containment vessel and other structures of the reactor complex, through the thick concrete wall of the reactor building. We evaluated the amount of material remaining in the fuel loading zone, and conclude that most of the original fuel materials have melted and dropped from the loading zone.